Komodifikasi Konten Tawuran Antar Kelompok Gangster di Kalangan Remaja di Jakarta Timur - Saputra, Alit Adi; Purwanto, Danang (Titian: Jurnal Ilmu Humaniora, 2025)
Gangster brawl content is widely consumed by the public, marked by high levels of Instagram engagement. This reality can bring opportunities for content commodification that generates financial gain through endorsement practices. This is because high engagement can attract advertisers to collaborate on endorsements. The researcher uses the Media Commodification perspective by Vincent Mosco. The main objective is to identify the causes and how the process of commodification of gangster brawl content occurs. Qualitative research methods with a case study approach and snowball sampling techniques. Primary data collection techniques through FGDs, in-depth interviews, and digital content observations. Data validity testing uses triangulation techniques. The results of the study show that the reality of brawl content commodification occurs through online gambling site endorsement practices and also the sale of gangster group identity merchandise as an advantage of having high engagement and prestige in the gangster brawl scene. Implications for community stakeholders can trigger preventive efforts for the surrounding environment related to new patterns of juvenile delinquency today, and have value for the authorities to enforce criminal law violations in this case strategically.  Abstract Konten tawuran gangster ramai dikonsumsi publik dengan ditandai tingkat engagement instagram yang tinggi. Realitas ini dapat membawa peluang terjadi komodifikasi konten yang menghasilkan keuntungan finansial melalui praktek endorsement. Sebab, engagement yang tinggi dapat menarik pengiklan untuk bekerja sama endorsement. Peneliti menggunakan perspektif Komodifikasi Media oleh Vincent Mosco. Tujuan utamanya mengidentifikasi penyebab dan bagaimana proses terjadinya komodifikasi konten tawuran gangster. Metode penelitian kualitatif dengan pendekatan studi kasus dan teknik pengambilan sampel snowball sampling. Teknik pengumpulan data primer melalui FGD, wawancara mendalam, dan observasi konten digital. Uji validitas data menggunakan teknik triangulasi. Hasil penelitian menunjukkan realitas komodifikasi konten tawuran terjadi melalui praktek endorsement situs judi online dan juga jualan merchandise identitas kelompok gangster sebagai keuntungan memiliki engagement dan prestise yang tinggi dalam skena tawuran antar gangster. Implikasi bagi stakeholder masyarakat, dapat memancing upaya preventif bagi lingkungan sekitarnya terkait pola baru kenakalan remaja masa kini, serta memiliki nilai bagi pihak berwenang guna penegakan pelanggaran hukum pidana kasus ini secara strategis.